2022
DOI: 10.3390/molecules27134001
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cytotoxicity of Portuguese Propolis Ethyl Acetate Fraction towards Renal Cancer Cells

Abstract: Renal cell carcinoma is the most lethal cancer of the urological system due to late diagnosis and treatment resistance. Propolis, a beehive product, is a valuable natural source of compounds with bioactivities and may be a beneficial addition to current anticancer treatments. A Portuguese propolis sample, its fractions (n-hexane, ethyl acetate, n-butanol and water) and three subfractions (P1–P3), were tested for their toxicity on A498, 786-O and Caki-2 renal cell carcinoma cell lines and the non-neoplastic HK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Our research group has previously reported the chemical composition of G18.EE and its fractions [ 43 ]. In general, the compounds found in the subfractions ( Table 2 ) fit well with what has been described for other Gerês propolis samples [ 40 , 42 , 43 ]. Moreover, some of the compounds identified here are present in other European propolis samples [ 64 ].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our research group has previously reported the chemical composition of G18.EE and its fractions [ 43 ]. In general, the compounds found in the subfractions ( Table 2 ) fit well with what has been described for other Gerês propolis samples [ 40 , 42 , 43 ]. Moreover, some of the compounds identified here are present in other European propolis samples [ 64 ].…”
Section: Discussionsupporting
confidence: 84%
“…Propolis has proven antitumor activity against several types of cancer [ 42 , 47 , 48 , 49 , 50 , 51 , 52 ] and, although scarce, some researchers demonstrated its anti-melanoma activity [ 43 , 53 , 54 ]. Some therapeutic options already exist for melanoma, but their effectiveness is still limited, mainly due to acquired resistance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations